Regional Variation in Attitude of Mental Health Professionals Towards Tackling Illicit Drug-use and Drug-related Disorders - Olubusayo Akinola; Wen-Hung Kuo; John Oswald; Olawunmi Obisesan (International Journal of Public Health Science (IJPHS), 2017)
This study sought to assess the attitudes of Mental Health Professionals (MHPs) towards tackling illicit drug use and drug-related disorders in Nigeria and to explore regional variations in attitude. Based on the validated Substance Abuse Attitude Survey (SAAS), a quantitative cross-sectional survey was conducted in a randomized sample of 292 MHPs practicing in neuropsychiatric hospitals and mental health departments of teaching hospitals from four geopolitical zones of Nigeria. A response rate of 81.1% was achieved. MHPs tended towards non-permissive, moralistic and stereotypic spectrum and exhibited distinctly defined attitude towards their professional role. The Kruskal-Wallis analysis established significant regional variation in the attitude of multidisciplinary MHPs, H (3)=18.727, p< .0001 reflecting a stochastic domination across the region; therefore a step-down follow-up analysis was conducted. This analysis revealed that the distribution of attitude total-score varies significantly between the South-south and the Southwestern region (p< .0001), the northeastern and southwestern region of the country (p< .028).  A holistic approach towards standardization of drug treatment and care that takes into consideration possible regional variation in attitudes of MHPs should be implemented to foster the reintegration and rehabilitation of drug-using populations into the mainstream society.